Renal Artery Dimensions and Variation on Computed Tomography Angiogram: A Cross-sectional Study. - Panta, Om Biju; Dhakal, Vivek; Giri, Shahjan Raj; Gurung, Bibek; Ghimire, Ram Kumar (Med Phoenix, 2022)
Introduction A knowledge of renal artery dimension is necessary for characterizing the physiological change as well as pathological process undergoing in the renal artery likely stenosis, ectasia, or aneurysm. This study aims to explore the anatomy of the renal artery with regards to its dimension, relation, and branching and identify the common anatomical variation. Materials and Methods The study was a retrospective hospital record-based study conducted during the period of one year from 2019 January to 2019 December. All abdominal CT angiograms were reviewed for renal artery anatomy and variation. Abnormal Abdominal CT angiograms were excluded from the study. Normal anatomy, dimensions, and variation of renal vasculature were assessed. Results A total of 110 patients included the inclusion criteria and was included in the study. The renal length and size of the renal artery were significantly larger on the left side. The renal artery diameter showed positive correlation with renal length (r= 0.432; p<0.001). No variation of the renal size of renal artery diameter was however noted with sex. Supernumerary arteries were seen in 33(30%) patients. The optimum cut-off value of renal artery diameter for predicting accessory renal artery was 5.35 or less which yielded a sensitivity of 75% and specificity of 70%. (AUC-0.79; p<0.001). When 4.15 mm was taken as cut-off, the specificity increased to 96% with a marked reduction in sensitivity to 3.6%. Conclusion Renal artery diameter is dependent on laterality, kidney size, and presence of accessory artery and independent of sex.